Testicular granulomatous vasculitis mimicking testicular torsion in an anti-neutrophil cytoplasmic antibody–associated vasculitis patient. (January 2019) - Suo, Liye; Perez, Luis Carlos; Finch, Christie Jean
Testicular vasculitis is uncommon and can be easily misdiagnosed. Early identification and treatment are essential for patient care. A 63-year-old man, presenting with testicular pain and swelling, had been treated with antibiotics for weeks. A month later, he developed severe left testicular pain and systemic symptoms. Scrotal ultrasound was suggestive of testicular torsion due to no blood flow. Pathology of the orchiectomy specimen demonstrated testicular granulomatous vasculitis involving small- to medium-sized arteries. Additional work-up of blood tests contained positive antinuclear, anti-proteinase 3 and anti-myeloperoxidase antibodies. Erythrocyte sedimentation rate and C-reactive protein were also elevated. Diagnosis of anti-neutrophil cytoplasmic antibody–associated vasculitis was made and prednisone was started. During more than 1-year follow-up, the patient's systemic symptoms were resolving gradually with no involvement of the other testis.